Ijtihad Bahtsul Masāil NU dalam Bidang Ekonomi - Abib Novriyanto; Moh Bahrudin; Syamsul Hilal (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
Ijtihad Bahtsul Masail Nahdlatul Ulama (NU) in the field of economics, which seeks to answer contemporary challenges while remaining rooted in the tradition of Islamic knowledge. NU's approach prioritizes the continuity of the transmission of Islamic knowledge through a legitimate and trusted chain, using classical fiqh books, especially the Shafi'i school of thought. The purpose of this study is to understand the relevance and effectiveness of collective ijtihad carried out by NU in answering modern economic issues such as Islamic banking, investment, e-commerce, and digital payment systems. The method used in this study is a literature study by reviewing literature related to classical fiqh books, journals, and relevant scientific articles. The results of the study show that Bahtsul Masail NU has made a significant contribution to developing Islamic economic law that is relevant to the development of the times. LBM NU not only answers contemporary issues, such as online investment and e-commerce, but also plays a role in forming sharia-based economic policies implemented by the community. However, this study also notes challenges, such as maintaining the consistency of the ijtihad method and answering complex issues without sacrificing the basic principles of sharia.